2005
DOI: 10.1002/ardp.200400993
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Mutations in TM2/TM3 in a D2 Dopamine Receptor Background Confirms the Importance of this Microdomain as a Selective Determinant of Para‐Halogenated 1,4‐Disubstituted Aromatic Piperazines

Abstract: We recently demonstrated that in the D4 dopamine receptor the aromatic microdomain that spans the interface of the second and third transmembrane (TM) domains influences the high affinity interactions of extremely D4-selective ligands possessing a 1,4-disubstituted aromatic piperazine/piperidine (1,4-DAP) structure. On the basis of their substructural features and patterns of sensitivity to mutations constructed in a D4 receptor background, the D4-selective 1,4-DAPs were categorized as having two distinct mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…First, it explains the discrepancy (ϳ100-fold differences) in the reported affinities of L-745,870 and several other structurally similar D 4 -selective 1,4-DAPs for the D 2 -V2.61(91)F mutant and thus resolves an apparent contradiction in the literature (Simpson et al, 1999;Floresca et al, 2005). Second, it demonstrates how key molecular interactions between a ligand and a specific GPCR microdomain are influenced by occupancy of an allosteric site.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…First, it explains the discrepancy (ϳ100-fold differences) in the reported affinities of L-745,870 and several other structurally similar D 4 -selective 1,4-DAPs for the D 2 -V2.61(91)F mutant and thus resolves an apparent contradiction in the literature (Simpson et al, 1999;Floresca et al, 2005). Second, it demonstrates how key molecular interactions between a ligand and a specific GPCR microdomain are influenced by occupancy of an allosteric site.…”
Section: Discussionmentioning
confidence: 70%
“…Although previous studies have revealed the affinity relationship between the discriminant structural features of 1,4-DAPs and the 1,4-DAP D 4 /D 2 selectivity-conferring positions 2.61(91), 3.28(110), and 3.29(111), the effects of mutations in this microdomain on the activity of 1,4-DAP ligands had not been described previously (Simpson et al, 1999;Schetz et al, 2000;Kortagere et al, 2004;Floresca et al, 2005). Therefore, because the D 2 -V2.61(91)F receptor exhibits sodium-sensitive affinity changes to 1,4-DAPs, we examined here the functional properties of L-745,870, L-750,667, and NGD 94-1 at the wild-type and D 2 -V2.61(91)F receptor.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations